Continuous Detecting Device and Method for Ammonia Gas Release in Concrete Mixed with Denitrified Fly Ash. Issue 1 (February 2021) - Zhang, Sijia; Zhang, Xiusong; Wu, Shuai; Kong, Xiangzhi; Wu, Kui
Abstract: The ammonia gas released from concrete mixed with denitrified fly ash has a negative impact on the performance of concrete, and is also hazardous to the health of constructors in closed spaces such as hydraulic tunnels and subways. The study of ammonia gas releasing law of concrete mixed with denitrified fly ash can provide a solution to eliminate these adverse effects. Moreover, ammonia gas releasing is a continuous and slow process, and there is no effective detection method at present. In order to solve the problem that ammonia gas release from concrete mixed with denitrified fly ash cannot be absorbed and detected continuously, in this paper, a continuous testing device for ammonia gas release from concrete is developed, which can adjust the temperature and wind speed in the test box to simulate the construction environment, vibration and hardening process, and realize the real-time detection of ammonia gas release from pouring to curing of concrete. The ammonia gas releasing law of concrete mixed with denitrified fly ash in the process of vibrating and hardening was tested. The results show that vibrating can accelerate ammonia gas releasing in concrete, and ventilation is beneficial to ammonia gas dissipation. The ammonia gas concentration in the test chamber decreases gradually and tends to zero with the increase of ventilation time. The total ammonia gas release from concrete increases significantly in the early hardening stage and gradually increases with the time, and finally tends to be stable. The release rate of ammonia gas in concrete accords with the exponential decay law.